2011
DOI: 10.1002/pmic.201100329
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of Hsp70 as a new Plk1 substrate in arsenic trioxide‐induced mitotically arrested cells

Abstract: We previously demonstrated that when arsenic trioxide (ATO)-induced mitotically arrested HeLa S3 cells (AIMACs) were treated with staurosporine (SSP) the cells rapidly exited mitosis. To better define the cellular targets and the underlying mechanisms of AIMACs, we applied 2-D DIGE followed by LC-MS/MS analysis and showed that SSP induced a significant change in the phosphoproteome of AIMACs. Among the proteins whose phosphorylation was modulated by SSP, we identified Hsp70, Rad 23B, and eukaryotic translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Immunoprecipitation-Western Blot Assay-The immunoprecipitation-Western blot assay was performed as previously described (35). Logarithmically growing cells were resuspended in 1 ml of radioimmune precipitation assay lysis buffer.…”
Section: Volume 290 • Number 36 • September 4 2015mentioning
confidence: 99%
“…Immunoprecipitation-Western Blot Assay-The immunoprecipitation-Western blot assay was performed as previously described (35). Logarithmically growing cells were resuspended in 1 ml of radioimmune precipitation assay lysis buffer.…”
Section: Volume 290 • Number 36 • September 4 2015mentioning
confidence: 99%
“…Furthermore, PLK-1 was also reported to phosphorylate eukaryotic translation initiation factor 4B (eIF4B) in response to arsenic tetroxide treatment in HeLa cells. eIF4B is required for the formation of the pre-initiation complex to initiate translation [21]. Although the study showed that PLK-1 phosphorylates eIF4B, no further detailed mechanism was delineated [21].…”
Section: Plk-1: Replication Transcription and Translationmentioning
confidence: 99%
“…eIF4B is required for the formation of the pre-initiation complex to initiate translation [21]. Although the study showed that PLK-1 phosphorylates eIF4B, no further detailed mechanism was delineated [21]. It will require additional biochemical studies to clarify the role of PLK-1 in the regulation of translation.…”
Section: Plk-1: Replication Transcription and Translationmentioning
confidence: 99%
“…Considering that Plk1 phosphorylation of HSP70 contributes to attenuation of high-dose arsenic trioxide (5 mM for 24 hours)-induced mitotic abnormalities, such as formation of elongated spindles, 5,10 and that Plk1 elevation leads to aerobic glycolysis, 13 we then asked whether low-dose arsenic affects the level of Plk1. Toward that end, proteins were prepared from liver, kidney, lung and bladder tissues of mice as described above.…”
Section: Low-dose Arsenic Induces Elevation Of Plk1mentioning
confidence: 99%
“…9 It was recently shown that HSP70 is a substrate of pololike kinase 1 (Plk1) in high-dose (5 mM for 24 h) arsenic trioxide-induced mitotically arrested cell and that its phosphorylation contributes to attenuation of arsenicinduced mitotic abnormalities. 10 Whether Plk1 also plays a critical role in low-dose (lower than 1 mM) arsenic-mediated phenotypes is not known. Plk1 has well documented roles in many mitotic-related events, such as centrosome maturation, bipolar spindle formation, sister chromatid segregation and cytokinesis.…”
Section: Introductionmentioning
confidence: 99%